Potential Therapies for Cystic Fibrosis: A Look at Cystic Fibrosis Transmembrane Conductance Regulator Correctors and Potentiators - Jones, Spencer G. (The Meducator, 2014)
Cystic Fibrosis (CF) is an autosomal recessive genetic disorder that is caused by a mutation of the anion channel termed the cystic fibrosis transmembrane conductance regulator (CFTR). Treatment for CF has improved over time; however, many therapies focus only on alleviating symptoms as they occur. There have been recent advances in therapies that repair mutant CFTR, including the administration of small molecules called CFTR modulators. CFTR modulators fall under two categories: correctors that prevent early degradation of CFTR and potentiators that increase conductance of existing CFTR. This review discusses the advantages of repairing mutant CFTR, some recent advances in treatment development, and the future of CFTR modulator therapy.